2018
DOI: 10.3232/sjss.2018.v8.n1.07
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of salinization and sodification in irrigated areas with limited soil data: Case study in southern Portugal

Abstract: Due to its high land productivity, irrigated agriculture has an increasing role in food production. In the Alentejo region (southern Portugal) the irrigated area has grown since the completion of the Alqueva dam in 2002. Climatic change patterns foreseen for the Mediterranean region (more heat extremes, less precipitation and river flow, increasing risk of droughts and decrease in crop yields) are prone to soil salinization and sodification in irrigated areas in the region. The Roxo dam has some of the higher … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 2 publications
0
8
0
Order By: Relevance
“…This limits the availability of water and oxygen for plants, as well as for the entire soil-food web (European Communities, 2009). In addition, very high Na + contents may have negative effects on plant nutrition (Alexandre et al, 2018). Therefore, management of sodic lands needs to address these soil physical constraints.…”
Section: Antropogenic Causesmentioning
confidence: 99%
“…This limits the availability of water and oxygen for plants, as well as for the entire soil-food web (European Communities, 2009). In addition, very high Na + contents may have negative effects on plant nutrition (Alexandre et al, 2018). Therefore, management of sodic lands needs to address these soil physical constraints.…”
Section: Antropogenic Causesmentioning
confidence: 99%
“…In contrast, [14] assessed soil salinity and the alteration of irrigation canals in the Alentiji area of the southern region of Portugal. They found that soil salinity does not pose a significant challenge; however, the likelihood of soil fertility affecting forthcoming irrigation cannot be discounted.…”
Section: Resultsmentioning
confidence: 99%
“…Although clay soils are more affected by sodicity, it should be considered that there are some soil properties, other than texture, that are significant in influencing the behavior of soils under sodification risk, namely, depth and thickness of the sodic horizons and clay mineralogy. For instance, the presence of high-activity clay minerals, like smectite, is likely to increase the soil susceptibility to sodification [83]. The analysis of the relationships between the RSO index and its indicators in high-risk areas showed a strong prevalence of flat and low slope terrain (Figure 11a), moderate-to-restricted soil drainage in Luvisols, Vertisols and Cambisols (Figure 11b,c), and annual crops irrigated with surface or sprinkler systems (Figure 11d,e).…”
Section: Sodification Risk Areasmentioning
confidence: 99%
“…Although clay soils are more affected by sodicity, it should be considered that there are some soil properties, other than texture, that are significant in influencing the behavior of soils under sodification risk, namely, depth and thickness of the sodic horizons and clay mineralogy. For instance, the presence of high-activity clay minerals, like smectite, is likely to increase the soil susceptibility to sodification [83].…”
Section: Sodification Risk Areasmentioning
confidence: 99%